1981
DOI: 10.1210/jcem-52-3-393
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Possible Mechanism for Deficiency of Nonsuppressible Insulin-Like Activity in Thalassemia Major*

Abstract: Previous studies have shown that serum levels of the somatomedin, nonsuppressible insulin-like activity (NSILA-S), are extremely low in patients with thalassemia major. Since these patients are not GH deficient, several other possible mechanisms for the reduced levels of NSIL-S have been explored. No evidence for the presence of NSILA inhibitors was obtained either in mixing experiments of normal serum and thalassemic sera or after acid gel chromatography of thalassemic sera. The high iron and ferritin levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0
2

Year Published

1986
1986
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 29 publications
2
14
0
2
Order By: Relevance
“…On the other hand, some authors did not find a depres sion of hepatic protein synthesis in thalassemic patients and suggest that the low serum somatomedin activity could be due to some other mechanisms rather than a gen eral liver impairment [30,34], These authors reported a specific iron-inhibitory effect on somatomedin synthesis as well as an increase in degradation rate [30].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, some authors did not find a depres sion of hepatic protein synthesis in thalassemic patients and suggest that the low serum somatomedin activity could be due to some other mechanisms rather than a gen eral liver impairment [30,34], These authors reported a specific iron-inhibitory effect on somatomedin synthesis as well as an increase in degradation rate [30].…”
Section: Discussionmentioning
confidence: 97%
“…In a recent cross-sectional survey of growth and sexual maturation among Chinese children with /?-thalassaemia major, growth retardation was found in 75% of the girls and 62% of the boys over 12 years of age with lack of sexual development in 50% of the boys and 37.5% of the girls (Kwan et al, 1995). In the adolescent thalassaemic patients, GH deficiency is rare but subnormal IGF-I levels have been reported in a significant proportion (Saenger et af., 1980;Herington et af., 1981;Werther et al, 1981). The low serum IGF-I levels, which fail to rise following exogenous GH, and the presence of normal GH reserve in these patients is suggestive of GH resistance (Werther et al, 1981).…”
mentioning
confidence: 95%
“…In the adolescent thalassaemic patients, GH deficiency is rare but subnormal IGF-I levels have been reported in a significant proportion (Saenger et af., 1980;Herington et af., 1981;Werther et al, 1981). The low serum IGF-I levels, which fail to rise following exogenous GH, and the presence of normal GH reserve in these patients is suggestive of GH resistance (Werther et al, 1981). A significant though modest improvement in growth response to G H has been reported in 8 short thalassaemic children with impaired GH 359 0 1995 Blackwell Science Ltd secretion (Scacchi et al, 1991).…”
mentioning
confidence: 97%
“…Endocrine studies in these patients have frequently but not always revealed the presence of normal thyroid function, and normal GH response to provocative stimuli (2)(3)(4)(5)(6)(7)(8)(9)). An adequate endocrine explanation for the short stature recently was provided with the demonstration of marked reduction of •somatomedin activity (10,11). The underlying defect in these patients seems to be an impaired human (h) GHreceptor interaction or a postreceptor defect, both of which would lead to impairment of GH-induced generation of somatomedin (10,11).…”
mentioning
confidence: 99%
“…An adequate endocrine explanation for the short stature recently was provided with the demonstration of marked reduction of •somatomedin activity (10,11). The underlying defect in these patients seems to be an impaired human (h) GHreceptor interaction or a postreceptor defect, both of which would lead to impairment of GH-induced generation of somatomedin (10,11). In a recent study, a 3-day course of exogenous hGH failed to cause the expected rise of somatomedin(s) in a group of children with thalassemia major (12).…”
mentioning
confidence: 99%